Experimental bounds on deformed muon lifetime dilation - Iarley P. Lobo; Christian Pfeifer; Pedro H. Morais (Physics Letters B)
We analyze Planck scale induced modifications of the relativistic time dilation using data from the Muon Storage Ring experiment at CERN. By examining the lifetimes of muons, we establish, for the first time, a constraint on such quantum gravity-inspired deformations using this channel. The magnitude of the effect indicates that the study of cosmic rays is a well suited arena for this scenario. We show, that the spectrum of muons would be significantly affected for particles at the PeV scale. Since this later observation of the effect of time dilation is more indirect compared to a direct lifetime measurement, we encourage to perform a high precision measurement of the muon lifetime as a function of the muon's energy.